Investigating the Impacts of a Task-Based Extensive Reading Program on Reading Ability in Thai High School Students - Samutkao, Wongsathorn; Chaturongakul, Panna (LEARN Journal: Language Education and Acquisition Research Network, 2025)
This study aimed at investigating the impacts of a Task-Based Extensive Reading (TBER) program on the reading abilities of Thai high school students at a demonstration school in Thailand. Nine Mattayomsuksa 6 students from a Math-English program, selected through purposive sampling, participated in this TBER program. In this program, each student was required to read eight graded readers and complete task-based post-reading activities after finishing each book. Data were collected through pre- and post-tests to assess the effectiveness of the TBER program. In addition, verbal reports and semi-structured interviews were used to explore students’ perceptions. The test results revealed that all students in the experimental group showed considerable improvements in their post-test scores, whereas the comparison group indicated variations in their post-test scores, with some students showing gains, others experiencing declines, and some demonstrating no change. Furthermore, the students in the experimental group reported that they perceived improvements in reading ability, vocabulary acquisition and confidence in reading English books. Moreover, reading habits were gradually developed through this program. The results of the study indicate that the effectiveness of extensive reading can be enhanced when it is integrated with task-based language teaching, with supporting evidence discussed further in this article.